2015
DOI: 10.1093/jnci/djv342
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy With Immunomodulatory Drugs in Multiple Myeloma: A Meta-Analysis and Systematic Review

Abstract: Thalidomide- or lenalidomide-based maintenance therapy improves PFS but not OS in MM and increases risks of grade 3-4 adverse events, including thromboembolism, peripheral neuropathy, neutropenia, and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…Maintenance therapy was found to improve progression-free survival and overall survival in MM patients, 65 but was associated with increased risk of grade 3-4 adverse events. 66 Based on this systematic review, data on HRQoL during maintenance treatment are sparse and inconclusive and HRQoL measurement should be a part of future protocols including maintenance therapy.…”
Section: Hrqol During Maintenance Therapy and Treatment Continuatiomentioning
confidence: 99%
“…Maintenance therapy was found to improve progression-free survival and overall survival in MM patients, 65 but was associated with increased risk of grade 3-4 adverse events. 66 Based on this systematic review, data on HRQoL during maintenance treatment are sparse and inconclusive and HRQoL measurement should be a part of future protocols including maintenance therapy.…”
Section: Hrqol During Maintenance Therapy and Treatment Continuatiomentioning
confidence: 99%
“…So how does myeloma present? Its clinical presentation covers a wide spectrum of diseases and includes a normocytic, normochromic anaemia in 75% of cases, bone pain in 60% of cases at diagnosis, most commonly affecting the back and chest, with the extremities less frequently involved, fatigue and weight loss 4. In 1/5th of cases, renal failure may be the presenting manifestation, as in our reported case, with light chain nephropathy and hypercalcaemia the main causes.…”
Section: Discussionmentioning
confidence: 53%
“…The plasma cells proliferate in the bone marrow and often result in extensive skeletal destruction with osteolytic lesions, osteopenia and/or pathological fractures. The median age at presentation is 66 years, with 10% of patients <50 years and 2% <40 years 4. Myeloma presents with non-specific symptoms, thus leading to a delay in diagnosis, ultimately resulting in early morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelosuppression was recognized with increased frequency as a significant adverse event in the phase 2 trial of lenalidomide for myeloma 4 and confirmed in subsequent metaanalysis. 5 Toxicity was especially frequent at higher doses in the setting of renal failure. 6 However, unlike alkylating chemotherapy, lenalidomide does not damage DNA, but rather acts through other mechanisms, including by changing protein levels by causing targeted degradation of transcription factors IKZF1 and IKZF3 by direct interaction [7][8][9] or through an oxidationdependent mechanism.…”
Section: Discussionmentioning
confidence: 99%